A Community Orthopaedic Residency Approach to Education and Training During the COVID-19 Pandemic. (January 2021) - Oguayo, Chris C.; Chu, Jennifer; Jones, Alan L.
Abstract : Background: The COVID-19 pandemic has rapidly affected all facets of everyday life including the practice of medicine. Hospital systems and medical practices have evolved to protect patients, physicians, and staff and conserve personal protective equipment and resources. Orthopaedic practices have been specifically affected by social distancing and stay at home guidelines, limiting in-office practice and elective surgery restrictions. This, in turn, has had an effect on resident education. Previous literature has been published regarding how academic programs have adjusted to these changes. However, the effects on smaller orthopaedic residencies with nonacademic faculty has not been discussed. The orthopaedic residency at Baylor University Medical Center of Dallas is a fifteen-resident program with a combination of hospital employed and private practice faculty. We adjusted our resident education in mid-March 2020 to keep residents safe while trying to maximize surgical and clinical education and outside research. Goals: Our goals were to come up with a plan allowed for continuing high-level patient care and resident education while protecting residents and limiting burnout. Model: We devised a four-team system with five-day call periods. Interactions between teams were strictly minimized. We also moved to a web-based academic curriculum and devised a system for safe resident participation in surgical cases. The model has been adjusted based on attending and resident feedback. Conclusion: Until we develop effective treatments or vaccination for COVID-19, there is a possibility that it will be an ongoing threat. Resident education must also adapt to the changing environment while continuing to provide residents safe opportunities for patient care, didactic education, and research. We believe we have come up with a sustainable, adaptable model for resident education during this challenging time.